2016
DOI: 10.1016/j.neuroscience.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic plasticity induced by group II metabotropic glutamate receptors via enhancement of high-threshold KV currents in sound localizing neurons

Abstract: Intrinsic plasticity has emerged as an important mechanism regulating neuronal excitability and output under physiological and pathological conditions. Here, we report a novel form of intrinsic plasticity. Using perforated patch clamp recordings, we examined the modulatory effects of group II metabotropic glutamate receptors (mGluR II) on voltage-gated potassium (KV) currents and the firing properties of neurons in the chicken nucleus laminaris (NL), the first central auditory station where interaural time cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 86 publications
1
7
0
Order By: Relevance
“…A strong molecular candidate is metabotropic glutamate receptor 2 (mGluR2), which is primarily expressed in SACs postsynaptically to bipolar cell synapses, but not in bipolar or ganglion cells (Cai and Pourcho, 1999; Koulen et al, 1996; Seebahn et al, 2008). mGluR2 activation is known to promote neuronal excitability by modulating voltage-gated conductances (Bischofberger and Schild, 1996; Hamlet and Lu, 2016; Ikeda et al, 1995; Knoflach and Kemp, 1998; Kupferschmidt and Lovinger, 2015; Saugstad et al, 1996; Taniguchi et al, 2013) and to influence spiking responses of DSGCs (Jensen, 2006). Nevertheless, the role of mGluR2 in SAC dendritic computation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A strong molecular candidate is metabotropic glutamate receptor 2 (mGluR2), which is primarily expressed in SACs postsynaptically to bipolar cell synapses, but not in bipolar or ganglion cells (Cai and Pourcho, 1999; Koulen et al, 1996; Seebahn et al, 2008). mGluR2 activation is known to promote neuronal excitability by modulating voltage-gated conductances (Bischofberger and Schild, 1996; Hamlet and Lu, 2016; Ikeda et al, 1995; Knoflach and Kemp, 1998; Kupferschmidt and Lovinger, 2015; Saugstad et al, 1996; Taniguchi et al, 2013) and to influence spiking responses of DSGCs (Jensen, 2006). Nevertheless, the role of mGluR2 in SAC dendritic computation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this notion, we recently observed that activation of mGluRs enhanced high voltage-gated K + channel currents in timing coding neurons in the auditory brainstem. Critically, the modulation was only detected under perforated patch recording but not under conventional whole-cell recording [54].…”
Section: Overview Of Mglurs Expression and Physiological Methodsmentioning
confidence: 99%
“…Therefore, the anti-homeostatic plasticity observed after hearing deprivation is unlikely a reversion to the pre-hearing status. Besides, the intrinsic neuronal properties of NL neurons are also regulated by mGluRs in a coding frequency-dependent manner (Hamlet and Lu, 2016 ). By using a technique that preserves intracellular signaling pathways (perforated patch-clamp recording), we reported that the high threshold K V currents in NL neurons are enhanced, with the strongest modulation in LF neurons.…”
Section: Mglurs In Avian Itd Pathwaymentioning
confidence: 99%
“…By using a technique that preserves intracellular signaling pathways (perforated patch-clamp recording), we reported that the high threshold K V currents in NL neurons are enhanced, with the strongest modulation in LF neurons. This mGluR enhancement of K V currents renders NL neurons the ability to follow high-frequency inputs, via an increase in the membrane outward rectification and sharpening of the waveform of APs (Hamlet and Lu, 2016 ). We propose that this modulation provides a feedforward modulatory mechanism that enhances temporal processing, especially when the peripheral input is of high intensity.…”
Section: Mglurs In Avian Itd Pathwaymentioning
confidence: 99%